An explicit analytical model for seismic performance of an unbonded post-tensioned precast segmental rocking hollow pier. (15th April 2018) - Wang, Zhen; Wang, Jing-Quan; Liu, Tong-Xu; Zhang, Jian
Highlights: An explicit theoretical model was derived for deformation capacity of the piers. Formulas were given to get key coefficients of the flag-shaped hysteretic model. A fiber model was used to calculate cyclic and dynamic response of the piers. Abstract: To avoid iterative calculation, an explicit analytical model was developed for the deformation capacity of an unbonded post-tensioned precast segmental rocking hollow pier and divided into three statuses: decompression status, yield status and large deformation status. The pier was regarded as an equivalent reinforced concrete monolithic pier at the decompression status, and the compression zone height at the base section was computed explicitly to make deformation calculation non-iterative at the other two statuses. A verified fiber model based on the OpenSees platform was proposed. The proposed deformation capacity model was validated with existing cyclic loading tests and the verified fiber model. A parametric study was conducted to determine the effects of the main design parameters on four coefficients of the idealized flag-shaped hysteretic model based on the proposed deformation capacity model. New formulas were proposed to determine the four coefficients through regression analysis. The flag-shaped hysteretic model with the coefficients determined by the proposed formulas was validated with cyclic loading tests and dynamic history analysis based on the fiber model. The results of this research show that the proposed model for deformation capacity may be simplified into two statuses, and it can serve as a tool to provide loading-deformation curves that have good agreement with experiments and the fiber model. The flag-shaped hysteretic model with the proposed coefficients can accurately predict the maximum displacement response and conservatively predict the dissipation energy capacity for the rocking pier under a strong earthquake shock.